Decolonising spaces of geographical knowledge production: 'Thinking geographically' with undergraduate geographers in the RGS‐IBG at Kensington Gore. Issue 3 (17th June 2022) - Jazeel, Tariq; Mackay, Anson; Evans, Sarah L.; Souch, Catherine
Abstract: This commentary is a response to the Area commentary by Mark Griffiths and Kate Baker, which draws focus on the problematic prominence of colonial material histories at the Royal Geographical Society (with IBG)'s Lowther Lodge site. We outline an undergraduate field trip – run collaboratively by University College London (UCL) and the RGS‐IBG since 2018 – for first‐year UCL geography students that aims to make them both aware of geography's problematic colonial histories, and party to the ways the discipline is changing and critically engaging with its past. Positioned at the intersections of teaching and research, we highlight this field trip because we believe it stands as an example of precisely the kind of decolonial engagement with the RGS‐IBG for which Griffiths and Baker call. Abstract : This commentary describes a decolonial field trip run jointly by UCL and the RGS‐IBG for UCL's first year undergraduate geography students.